2-Arylacetamido-4-phenylamino-5-substituted pyridazinones as formyl peptide receptors agonists; Bioorganic & Medicinal Chemistry; Vol. 24, Iss. 11 - Vergelli C. Claudia; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Ciciani G. Giovanna; Cilibrizzi A. Agostino; Crocetti L. Letizia; Giovannoni M. P. Maria Paola; Guerrini G. Gabriella; Iacovone A. Antonella; Kirpotina L. N. Liliya Nikolaevna; Khlebnikov A. I. Andrey Ivanovich; Ye R. D. Richard; Quinn M. T. Mark (2016, 2016)
Title screen